Clinically defined subgroups of mycosis fungoides display differing histopathological features at initial biopsy. Issue 12 (2nd December 2018) - Wehkamp, Ulrike; Weichenthal, Michael; Egberts, Friederike; Schwarz, Thomas; Klapper, Wolfram; Oschlies, Ilske
Abstract: Most patients with mycosis fungoides (MF) remain in early disease stages but some progress to tumor stage. The individual course of the disease cannot be predicted. We wanted to assess the clinical and histological characteristics of the first available biopsy. An end-of-spectrum approach with two groups was used, comparing MF remaining long-term stable in T1a ('MF stable') and MF with later tumor development or present T3 stage ('MF tumor'). The clinical and histomorphological features of the initial skin biopsy were compared. Patients in the 'MF tumor' group presented initially with higher disease stages. The first biopsies of 'MF tumor' patients showed significantly higher infiltrate density and depth, more large cells and a higher proliferative index. In summary, long-term stable MF seems to differ in clinical and histopathological parameters from MF with T3 evolution/presence already at the time point of the initial biopsy. Our findings might indicate a predetermined biologic behavior.